2004
DOI: 10.1017/s0952836904004984
|View full text |Cite
|
Sign up to set email alerts
|

Adult female survival, population trend, and the implications of early primiparity in a capital breeder, the southern elephant seal (Mirounga leonina)

Abstract: Adult female survival as a potential proximate factor responsible for observed changes in southern elephant seal Mirounga leonina populations was investigated. We compared the survival rate estimates from mark-recapture data for female elephant seals from the Marion Island population (using program MARK) for two periods (pre-and post-decline) during the past 15 years and with estimates from another population in southern Argentina, which had increased steadily during the same period. Survival of prime-age adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 91 publications
4
90
6
Order By: Relevance
“…Pistorius et al (2004) found no significant age-dependent variation in survival of parous southern elephant seal females from our study population. Age-parameters were consequently not considered in our present analysis.…”
Section: Data Analysescontrasting
confidence: 72%
See 4 more Smart Citations
“…Pistorius et al (2004) found no significant age-dependent variation in survival of parous southern elephant seal females from our study population. Age-parameters were consequently not considered in our present analysis.…”
Section: Data Analysescontrasting
confidence: 72%
“…Similar to other sites (Guinet et al 1999;Slip & Burton 1999), the Marion Island (46°54'S, 37°45'E; located in the southern Indian Ocean, approximately 2180 km southeast of Cape Town, South Africa; Fig. 1) population has now stabilized (Pistorius et al 2004). An intensive demographic study initiated on the small population at Marion Island in 1983 has yielded consistent mark-recapture data.…”
Section: Introductionmentioning
confidence: 56%
See 3 more Smart Citations